Expedient Synthesis of Terminal Vinylphosphonates by Palladium-Catalyzed C−C Cross-Coupling Reactions of (1-Halovinyl)phosphonates - Fang, Yewen; Zhang, Li; Jin, Xiaoping; Li, Jinjian; Yuan, Meijuan; Li, Ruifeng; Gao, Haoqi; Fang, Jianghua; Liu, Yuyan (Synlett, 2015)
An efficient new synthetic route to (1-arylvinyl)phosphonates is presented. A wide range of (1-arylvinyl)phosphonates were prepared in good to excellent yields (79–99%) by using a palladium(II) acetate–organophosphine catalyst system. The protocol can be effectively scaled up without deleterious effects. The use of a (1-chlorovinyl)phosphonate as the electrophilic coupling partner was demonstrated for the first time.
Keywords: cross-coupling; phosphonates; palladium; catalysis; arylation